2004
DOI: 10.2307/3583182
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance Rate of HIV Testing among Women Seeking Induced Abortion in Benin City, Nigeria

Abstract: Although the campaign against HIV has been intensive, it has been focused mainly on the public health implications. Little or no attention is specifically directed at encouraging the public to know their HIV serostatus. The actual public health burden due to this infection is therefore not known. Accurate data on the health burden is critical for national planning on preventive and other interventional measures. Using a semi-structured self-administered questionnaire, we interviewed 1051 women seeking induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…The sample size was calculated using the Kish Leslie formula. 16 We estimated a robust sample size of 174 participants, approximated to 180, using a power calculation based on an expected prevalence of 13% for HIV screening acceptance 17 at a confidence interval of 95%. 18 Survey questionnaires were distributed through an electronic medium using the email contacts of all the international students from the listserv of all international students available at the Center for International Studies.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was calculated using the Kish Leslie formula. 16 We estimated a robust sample size of 174 participants, approximated to 180, using a power calculation based on an expected prevalence of 13% for HIV screening acceptance 17 at a confidence interval of 95%. 18 Survey questionnaires were distributed through an electronic medium using the email contacts of all the international students from the listserv of all international students available at the Center for International Studies.…”
Section: Methodsmentioning
confidence: 99%
“…HIV Prevalence and projections (adapted from FMOH sentinel report, 2003) regularly practiced unprotected sex, although all were aware of HIV/AIDS. Only 13% of them accepted to be tested for HIV [39]. In the same city, Offor et al reported a mother to child transmission in 33.3% of 246 women reporting for delivery [40].…”
Section: Transmission/risk Factorsmentioning
confidence: 99%
“…Some people however are afraid of testing for several reasons. This was seen in a study that showed only 13% of women accepting to be tested, among 1,051 induced abortion seekers in Benin City [39]. Good counseling before testing would greatly reduce this trend, apart from psychologically preparing the patient.…”
Section: Diagnosismentioning
confidence: 99%
“…According to Bartlett (2008) most individuals who are at the highest risk for HIV do not realize that they are at risk. Enosolease & Offor (2004) notes that high knowledge about HIV/AIDS do not necessarily translate to positive attitude towards HIV. Knowledge and attitude were positively correlated, which means the more people are aware of HIV, the more positive their attitude towards HIV and those living with HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%